THE ASEAN POLITICAL-SECURITY COMMUNITY: ASEAN SECURITY COOPERATION ON COMBATING TRANSNATIONAL CRIMES AND TRANSBOUNDARY CHALLENGES - Kusumaningrum, Adi (UI Scholars Hub, 2013)
The Asean Security Community (ASC) is a framework to facilitate political and security cooperation in ASEAN. The ASC is a framework based on the idea of comprehensive security with the strategic thrusts of conflict prevention, peaceful conflict resolution, and post-conflict peace building. A framework of this nature represents one of the ultimate goals of ASEAN, which has achieved a record of political cooperation since its inauguration. All nations of Southeast Asia except Timor Leste are now members of ASEAN. There are any ASEAN’s Security Challenges, such as old and new insurgencies - southern Philippines, southern Thailand, Myanmar, West Papua, political uncertainty and instability - Myanmar, Thailand, inter-state disputes and tensions - Thai-Cambodia border, South China Sea conflict, power shift and great power rivalry - China/US, China-India, China-Japan, and transnational/non- traditional security threats – terrorism, transboundary haze, maritime piracy, pandemics, transnational crime, drug trafficking, people smuggling, natural disasters). This paper disscuss abaut security cooperation in ASEAN and some achievements of ASEAN as regional organization on combating transnational crimes and transboundary challenges.